Unveiling the endogenous CRISPR-Cas system in Pseudomonas aeruginosa PAO1 - Delgado-Nungaray, Javier Alejandro; Figueroa-Yáñez, Luis Joel; Reynaga-Delgado, Eire; Corona-España, Ana Montserrat; Gonzalez-Reynoso, Orfil (PloS one, 2024)
Multidrug resistance in Pseudomonas aeruginosa , a high-priority pathogen per the World Health Organization, poses a global threat due to carbapenem resistance and limited antibiotic treatments. Using the bioinformatic tools CRISPRCasFinder, CRISPRCasTyper, CRISPRloci, and CRISPRImmunity, we analyzed the genome of P . aeruginosa PAO1 and revealed an orphan CRISPR system, suggesting it may be a remnant of a type IV system due to the presence of the DinG protein. This system comprises two CRISPR arrays and noteworthy DinG and Cas3 proteins, supporting recent evidence about the association between type IV and I CRISPR systems. Additionally, we demonstrated a co-evolutionary relationship between the orphan CRISPR system in P . aeruginosa PAO1 and the mobile genetic element and prophages identified. One self-targeting spacer was identified, often associated with bacterial evolution and autoimmunity, and no Acr proteins. This research opens avenues for studying how these CRISPR arrays regulate pathogenicity and for developing alternative strategies using its endogenous orphan CRISPR system against carbapenem-resistant P . aeruginosa strains.